SYNTHESIS AND IDENTIFICATION OF GRAPHITE OXYNITRATE - ШОЛОГОН, В. І.; ВАХІТОВ, Р. А.; ТАРАН, Н. А.; ВАХІТОВА, Л. М.; БЕССАРАБОВ, В. І. (Technologies and Engineering, 2023)
Purpose. Investigation of the patterns of formation of graphite oxynitrate in the graphite-nitric acid system with the identification of the reaction product by varying the synthesis time and the ratio of reagents. Methodology. Graphite oxynitrate was obtained by oxidation of natural flake graphite with fuming nitric acid. The structure of the reaction product was determined by FTIR spectroscopy and X-ray phase analysis. Findings. The processes of graphite oxidation and intercalation in the graphite-fuming HNO3 system with the procedure of isothermal exposure of the reaction mixture were studied. It has been established that when graphite interacts with fuming nitric acid at a temperature of 60–95°C, followed by isothermal holding in a temperature regime of 20–30°C, a new hybrid graphite compound is formed – graphite oxide nitrate. This product is a graphite oxide of the second and third degrees of intercalation with fragments of graphene lattices and single-walled carbon nanotubes, intercalated with nitrate anions and solvated with nitric acid. The optimal conditions for the synthesis of graphite oxynitrate are determined: the time of stirring the reaction mixture of graphite-fuming nitric acid is 10 min; temperature regime of the oxidation process – intercalation is 85 °C; HNO3: graphite ratio is 0.4–0.5 cm3/g; duration of isothermal exposure – 24 hours. According to IR-data, structural fragments of graphite nitrate are represented by intralattice ion pairs of polyarene cations (or radical cations) with intercalated nitrate anions. In turn, graphite oxide structures are represented by layers of polyarenes (graphenes) functionalized with oxygen groups: hydroxyl, epoxy, quinoid, simple, lactone, etc. The results obtained make it possible to recommend graphite oxynitrate as a promising, long-term stable nanomaterial for new efficient technologies of graphene oxide. Originality. Graphite oxynitrate, a hybrid graphite structure of graphite oxide intercalated with nitrate anions, was obtained for the first time. Practical value. The optimal conditions for the synthesis of graphite oxynitrate are determined, which can be used in the development of appropriate nanotechnologies.